PEMIKIRAN DAN TINGKAHLAKU KEWIRAUSAHAAN WIRAUSAHAWAN MAKANAN TRADISIONAL KHAS MINANGKABAU SUMATERA BARAT, INDONESIA - Rustani, Istetimurni; Zulkarnaini, Noviarti (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2016)
Entrepreneurial thinking and entrepreneurial behavior among traditional food entrepreneurs are important factors which ccntribute to their innovativeness. These Minangkabau ethnic traditional food entrepreneurs produced traditional Minangkabau food mainly spicy and savory. However, their food menu is already popular in the world. This study aimed to identify the profile of these entrepreneurs, their entrepreneurial thinking level and entrepreneurial behavior. The design of this study is a case study method. The data collection technique used was an indepth interview among those twenty one traditional food entrepreneurs in west Sumatera, Indonesia. The findings of this research revealed that 81% of the entrepreneurs is family business. For the level of entrepreneurial behavior, the finding showed that it is high level. For the level of entrepreneurial thinking, it is just moderate level. The findings implied that entrepreneurial thinking and entrepreneurial behavior are the important factors that contribute to being innovative entrepreneurs. Based on these findings, it requires a strong commitment from government and private sector to deliver strategy for developing innova tive entrepreneurs.